Calculation and Comparison of Stress Concentration Factors in Composite Inverted-tooth Chain Link Plates with Various Dimensions - Pihtili, Hasim (Sage Publications Ltd, 2008)
The effect of fiber type and direction on the level of stress concentration factors, k, created by the presence of a notch was investigated for inverted-tooth chain link plates made of unidirectional and symmetric cross-ply laminates loaded on or off axis. The finite element (FE) method was used for this purpose utilizing triangular elements under plane stress conditions. Analysis was performed for three different fiber reinforcements of epoxy matrix: glass, graphite, and boron. Typical mechanical properties reported in the literature for graphite-epoxy, glass-epoxy, and boron-epoxy were used in calculations. The accuracy of the FE code utilized was first checked by calculating the stress concentration factors for an isotropic plate made of steel. The results which were determined by the computer-based FE method were compared with experiment results. It was seen that results agree well with strain-gauge and photo elastic measurements.
Keywords: composite materials; finite element (FE); inverted-tooth chains; stress concentration; optimization